PROCESS HANDLING CASES OF DRUG ABUSERS FROM CRIMINALIZATION TO DECRIMINALIZATION - Efesus DM Sinaga; M. Musa; Abd Thalib; Ellydar Chaidir (International Conference On Law And Social Sciences, 2024)
The rise of narcotics among the community which makes victims of drug abuse users is increasing and the prevention of a user who is currently still not leveled. The Directorate General of Corrections of the Ministry of Law and Human Rights noted that prisons in Indonesia as of July 2, 2023 were inhabited by 187,183 prisoners and prisoners who continued to increase. Whereas the capacity of prisons in Indonesia is only 93,236 people. This means that prisons in Indonesia have experienced overload. For the article Handling Narcotics Abuse Cases From Criminalization to Decriminalization. Which aims to find out the decriminalization of drug abusers in the construction of positive law in Indonesia and the decriminalization arrangements in the Integrated Assessment Team (IAT) of narcotics in Indonesia. The result of his writing is that victims of narcotics abusers and addicts are placed into medical and social rehabilitation institutions, and based on articles 54 and 55 it is clearly stated that narcotics addicts must receive treatment and/or care through medical and social rehabilitation.